Sonochemical synthesis of nanostructured nickel hydroxide as an electrode material for improved electrochemical energy storage application - Numan, A.; Duraisamy, N.; Omar, F.S.; Gopi, D.; Ramesh, K.; Ramesh, S. (Elsevier, 2017)
A facile and fast approach for the synthesis of a nanostructured nickel hydroxide (Ni(OH)2) via sonochemical technique is reported in the present study. The X-ray diffraction results confirmed that the synthesized Ni(OH)2 was oriented in β-phase of hexagonal brucite structure. The nanostructured Ni(OH)2 electrode exhibited the maximum specific capacitance of 1256 F/g at a current density of 200 mA/g in 1 M KOH(aq). Ni(OH)2 electrodes exhibited the pseudocapacitive behavior due to the presence of redox reaction. It also exhibited long-term cyclic stability of 85% after 2000 cycles, suggesting that the nanostructured Ni(OH)2 electrode will play a promising role for high performance supercapacitor application.